A Thailand case study based on quantitative assessment: Does a national lead agency make a difference in pre-hospital care development in middle income countries? - Paibul Suriyawongpaisal (2018)
© 2014 Suriyawongpaisal et al. Background: Emergency Medical Institute of Thailand (EMIT) has been established as a national lead agency to improve emergency medical service systems since December 2008. However up to now, there has not been any published systematic assessment of its performance to guide further policy decisions. Methods: This study assesses the 4-year pre-hospital care coverage and performance in Thailand after EMIT establishment. The assessment makes use of 1,171,564 records from a national data set for pre-hospital care i.e., Information Technology for Emergency Medical Service System (ITEMS) in 2012. Results: Comparing with historical data, we found evidence indicating the national lead agency making differences in two basic requirements of pre-hospital care i.e., the coverage was increased by at least 1.4 times higher than the majority reported figures among 11 out of the total 13 regions of the country at baseline; and mean total response time for critical-coded patients, the longest in our study, is 1.6 times shorter than previously reported figure in 2008 (48.46 minutes). Analysis of the national data set also revealed quite substantial missing values indicating a need for further improvement. When historical data was not available, we compared our findings with international figures. Over triage rate of 28.4% for advanced life support (ALS) ambulance was found which is roughly a third of that reported in Taiwan. Almost all patients were stabilized and/or treated regardless of being transferred to hospitals in contrast to the scenarios in the U.S. systems which may probably be due to different payment mechanism. Relying on circumstantial evidences, we identified probable stagnation in pre-hospital care coverage for patients visiting emergency department after the establishment of the lead agency. Conclusions: This national data assessment shows progression in certain basic pre-hospital care requirements in Thailand. However, it needs regular systematic evaluation and there is still room for improvement of pre-hospital care systems such as increasing coverage, more equitable distribution of the coverage, faster response times, especially for patients with critical code, information system, cost-effectiveness study as well as further specific qualitative researches to guide further development of policy and intervention.